Effect of caustic paste, direct fire alone or combined with flunixin meglumine during disbudding of holstein calves on physiological and behavioral parameters (Veterinary Science, 2024)
The aim of this study was to determine the effects of different disbudding methodologies in Holstein calves on behavioral and physiological parameters related to pain. Twenty-five calves under artificial rearing with an average of 22 ± 3 days of age and 48.9 ± 8.8 kg of live weight were randomly assigned to three treatments: Tc, control disbudding with a thermal method using hot iron, Ta: disbudding with hot iron + flunixin meglumine (2.2 mg/kg intramuscular, 20 minutes prior to the procedure and Tp: disbudding using caustic paste. After disbudding and for 30 minutes, the number of times that each animal performed the following behaviors was recorded: Shakes head, scratches the head, rubs the head, presses the head, shakes the body, grooms, jumps, runs and bleats. Then the heart and respiratory rates were measured. In the Tp group the frequencies of shaking the head (p < 0. 0003), scratching the head (p< 0.0009), rubbing the head (p
Keywords: Dehorning; Dairy farm; Pain relief